2009
DOI: 10.3892/ijo_00000515
|View full text |Cite
|
Sign up to set email alerts
|

Punicic acid is an ω-5 fatty acid capable of inhibiting breast cancer proliferation

Abstract: Abstract. Pomegranate extracts have been used as anticancer agents and they contain a large number of potentially bioactive substances. Punicic acid is an ˆ-5 long chain polyunsaturated fatty acid found in Punica granatum (pomegranate) seed oil. A number of long chain fatty acids have been reported to have cancer preventive actions. Here we investigated the potential ability of punicic acid to affect growth of both an estrogen insensitive breast cancer cell line and an estrogen sensitive cell line developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Cytotoxic effect of CLnA isomers of conjugated triene type was more evident than this of conjugated diene type, which is partially conjugated (Koba et al, 2007a). It is said that the mechanism of cytotoxic effect of CLnA is connected with the lipid peroxidation, which causes an activation of protein kinase C (PKC) responsible for apoptosis induction and proliferation inhibition (Grossmann et al, 2010). Nevertheless, the addition of antioxidant compounds (e.g., α-tocopherol) decreased these beneficial properties of CLnA isomers (Shinohara et al, 2012).…”
Section: Anticancerogenic Propertiesmentioning
confidence: 99%
“…Cytotoxic effect of CLnA isomers of conjugated triene type was more evident than this of conjugated diene type, which is partially conjugated (Koba et al, 2007a). It is said that the mechanism of cytotoxic effect of CLnA is connected with the lipid peroxidation, which causes an activation of protein kinase C (PKC) responsible for apoptosis induction and proliferation inhibition (Grossmann et al, 2010). Nevertheless, the addition of antioxidant compounds (e.g., α-tocopherol) decreased these beneficial properties of CLnA isomers (Shinohara et al, 2012).…”
Section: Anticancerogenic Propertiesmentioning
confidence: 99%
“…In fact, CLnAs have been shown to possess anti-inflammatory [14][15][16], anti-obesity [14,17,18], anti-diabetic [19,20] and anti-cancer activities [1,2,[21][22][23]. Specifically, PunA has been reported to exert a strong anti-cancer activity, both in vitro [7,[24][25][26] and in vivo [4,27,28]. PunA anti-cancer activity is thought to be associated with lipid peroxidation [7].…”
Section: Introductionmentioning
confidence: 99%
“…These acids are rarely found in animal fats and are not commonly found in vegetable oils (Özgül‐Yücel, 2005 ). Studies have shown punicic acid has beneficial health effects such as antitumor activities, immune system regulators, anti‐atherosclerosis, and serum lipid lowering (Carvalho et al., 2010 ; Grossmann et al., 2010 ). Therefore, with high levels of punicic acid, the studied pomegranate seed oil may also have health‐benefiting properties.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported on the levels of phenolics in pomegranate seed oils. Phenolics of seed oils of six pomegranate cultivars grown in Georgia ranged from 849 to 911 mg/kg (Grossmann et al., 2010 ). In other studies, phenolics of pomegranate seed oils grown in South Africa (Kaseke et al., 2021 ) and Serbia (Drinić et al., 2020 ) were reported at 1200 and 160 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%